Modeling and experimental analysis of acoustic cavitation bubbles for Burst Wave Lithotripsy. (November 2015) - Maeda, Kazuki; Kreider, Wayne; Maxwell, Adam; Cunitz, Bryan; Colonius, Tim; Bailey, Michael
Abstract: Cavitation bubbles initiated by focused ultrasound waves are investigated through experiments and modeling. Pulses of focused ultrasound with a frequency of 335 kHz and a peak negative pressure of 8 MPa is generated in a water tank by a piezoelectric transducer to initiate cavitation. The pressure field is modeled by solving the Euler equations and used to simulate single bubble oscillation. The characteristics of cavitation bubbles observed by highspeed photography qualitatively agree with the simulation results. Finally, bubble clouds are captured using acoustic B-mode imaging that works synchronized with high-speed photography.